2014
DOI: 10.3928/1081597x-20140903-02
|View full text |Cite
|
Sign up to set email alerts
|

Non-topography–guided PRK Combined With CXL for the Correction of Refractive Errors in Patients With Early Stage Keratoconus

Abstract: Combined non-topography-guided PRK and CXL is an effective and safe option for correcting mild refractive error and improving visual acuity in patients with early stable keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 26 publications
1
10
0
3
Order By: Relevance
“…All evaluated visual and refractive parameters demonstrated highly significant improvement after the surgery in both studied groups (all P < 0.001) at 6 months after surgery with no significant changes till the end of follow-up indicating plateauing and stabilization of outcome (Table 3). On the other hand, in one study carried in early cases of keratoconus using non-topo guided PRK with CXL, the authors demonstrated significant improvement in the UDVA, spherical equivalent, and cylinder while the CDVA remained stable [20]. The significant visual improvement obtained in our study in both UDVA and CDVA was due to the reduction of the spherocylindrical error and the minimization of HOAs.…”
Section: Discussionsupporting
confidence: 56%
“…All evaluated visual and refractive parameters demonstrated highly significant improvement after the surgery in both studied groups (all P < 0.001) at 6 months after surgery with no significant changes till the end of follow-up indicating plateauing and stabilization of outcome (Table 3). On the other hand, in one study carried in early cases of keratoconus using non-topo guided PRK with CXL, the authors demonstrated significant improvement in the UDVA, spherical equivalent, and cylinder while the CDVA remained stable [20]. The significant visual improvement obtained in our study in both UDVA and CDVA was due to the reduction of the spherocylindrical error and the minimization of HOAs.…”
Section: Discussionsupporting
confidence: 56%
“…Several clinical reports demonstrated stability in corneas that had undergone a combination of CXL and PRK, either sequentially or combined. Patients experienced improvement in spherical equivalent (SE), defocus equivalent, uncorrected and best corrected visual acuity, high order aberrations and Kmax with stabilization of keratoconus progression during a follow up period of 12–24 months [ 121 124 ].…”
Section: Reviewmentioning
confidence: 99%
“…It is important to note that meaningful comparisons of the current study outcomes to published literature related to TG laser treatment are difficult given the significant differences in the magnitude of corneal ectasia (from early to advanced keratoconus) across studies 6,9,13,15. In addition, the TG ablations are centered on the corneal vertex and encompass the whole cornea, whereas WG ablations are centered on the pupil; therefore, it may be futile to compare the current study results with literature.…”
Section: Discussionmentioning
confidence: 99%